ESTIMATION OF THE CARBON BIOMASS STORED IN THE FOREST ECOSYSTEM OF THE BILLINGS RESERVOIR-SP - Silva, Cleber Vitorio; Silva, Karina Arruda; Abreu, Luiz Santos; Silva, Elenice Rachid da; Almeida, Josimar Ribeiro (Revista Internacional de Ciências, 2019)
Global warming has become international concern, culminating with the ratification of the Kyoto Protocol which includes definitions and objectives of the sustainable development mechanisms and features that make it easier for the industrialized countries to jointly compensate for their polluting greenhouse gas emissions. São Paulo is a state known for its industrial development and distortion of the green areas in ecosystems associated with the Atlantic Forest biome. In the middle of this chaotic scenery lies the Billings reservoir in São Bernardo do Campo-SP, its forest ecosystem is the provider of numerous environmental services. Quantification of biomass (Bwood) of stems resulted in estimates of 113.73.ha-1, which corresponded to 56.87 tC.ha-1. The estimates obtained for the forest ecosystem of the reservoir can be used as a reference for the establishment of forest restoration projects under the Clean Development Mechanism established the Kyoto Protocol.